PENTINGNYA MENGARAHKAN PENGGUNAAN BAHASA INDONESIA YANG BAIK PADA ANAK USIA DINI - Putri Mei Niagana; Desma Yuliadi Saputra; Rina Andriani (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
This study aims to examine the importance of directing the use of good Indonesian in early childhood. Indonesian is the primary means of communication and an important tool in cognitive, social, and emotional development in children. This study used a qualitative method with a case study approach in several early childhood education institutions (PAUD). The results showed that directing the use of good Indonesian from an early age has a positive impact on children's language skills, including increased vocabulary, the ability to construct effective sentences, and confidence in communication. In addition, this study also identified effective strategies and methods in developing language skills in early childhood through play activities, storytelling, and structured social interactions. The implication of this study is the need to increase awareness and training for teachers and parents in providing good and appropriate Indonesian language guidance to support children's holistic development.